Effects of Moringa oleifera leaves on hemoglobin and serum retinol levels and underweight status among adolescent girls in rural Bangladesh - Khanam, Mansura; Sanin, Kazi Istiaque; Ara, Gulshan; Sultana Rita, Razia; Boitchi, Anika Bushra; Farzana, Fahmida Dil; Haque, Md. Ahshanul; Ahmed, Tahmeed (Frontiers in Nutrition, 2022)
Objectives: Moringa oleifera has been used for centuries due to its medicinal properties and health benefits. The plant has antifungal, anti-viral, and anti-inflammatory properties. We aimed to evaluate the effect of consumption of Moringa leaves, along with a regular diet on serum haemoglobin and retinol and underweight status among rural Bangladeshi adolescent girls. Methods: This school-based quasi-experimental study involved 226 adolescent girls (12-14 years-old). Intervention group (n=113) received a meal comprising rice, concentrated dal, and fried potato with Moringa pakora (oil-fried snack); the control group (at a different school in an adjacent area with similar population demographics) received calorie-matched meal without Moringa pakora for 6 months. We used generalized liner regression (GLM) analysis, to explore the effect of the intervention among the groups between baseline and endline. Results: Mean age of the intervention and control groups were 12.7±0.7 and 13.3±0.8 years, respectively. After adjusting for maternal education, absenteeism, asset index, BMI-for-age Z-score, GLM regression showed significant positive changes in haemoglobin (intervention vs. control: coef= 0.41, P=0.010) and serum retinol (Coef=0.27, P=0.00). No significant changes in weight was observed between groups. Conclusion: Consumption of Moringa leaves has the potential to improving haemoglobin and serum retinol level and should be encouraged as regular diet.